2004
DOI: 10.1155/s1110724304306017
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to Vitronectin and Collagen I Promotes Osteogenic Differentiation of Human Mesenchymal Stem Cells

Abstract: The mechanisms controlling human mesenchymal stem cells (hMSC) differentiation are not entirely understood. We hypothesized that the contact with extracellular matrix (ECM) proteins normally found in bone marrow would promote osteogenic differentiation of hMSC in vitro. To test this hypothesis, we cultured hMSC on purified ECM proteins in the presence or absence of soluble osteogenic supplements, and assayed for the presence of well-established differentiation markers (production of mineralized matrix, osteopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
319
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 372 publications
(345 citation statements)
references
References 37 publications
23
319
2
1
Order By: Relevance
“…Collagen VI is necessary for collagen I production in osteoblast like cells (Harumiya et al, 2002) and interlukin-4-dependent mineralization of human periosteal cells (Ishibashi et al, 1999). Likewise fibronectin, which supports attachment and spreading of hMSC and osteoblasts (Salasznyk et al, 2004b;Ogura et al, 2004;Pistone et al, 1996), is secreted by osteoblasts early in development, and may act to help organize the osteoid matrix by binding to collagen I in mature bone tissue (Nordahl et al, 1995). Damsky and colleagues have demonstrated that osteoblast/fibronectin interactions supply a necessary regulatory signal essential for osteogenic gene expression, with fibronectin possibly playing a role in the recruitment of osteoblast precursor cells (Globus et al, 1995;Moursi et al, 1996;Globus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen VI is necessary for collagen I production in osteoblast like cells (Harumiya et al, 2002) and interlukin-4-dependent mineralization of human periosteal cells (Ishibashi et al, 1999). Likewise fibronectin, which supports attachment and spreading of hMSC and osteoblasts (Salasznyk et al, 2004b;Ogura et al, 2004;Pistone et al, 1996), is secreted by osteoblasts early in development, and may act to help organize the osteoid matrix by binding to collagen I in mature bone tissue (Nordahl et al, 1995). Damsky and colleagues have demonstrated that osteoblast/fibronectin interactions supply a necessary regulatory signal essential for osteogenic gene expression, with fibronectin possibly playing a role in the recruitment of osteoblast precursor cells (Globus et al, 1995;Moursi et al, 1996;Globus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These cells are able to differentiate along several committed phenotypes including osteogenic [1][2][3], chrondogenic [4], adipogenic [5], cardiogenic [6], and neurogenic [7,8] lineages in response to stimulation by multiple environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Cell contact with extracellular matrix (ECM) proteins plays a critical role in regulating hMSC osteogenesis [3,[9][10][11]. Specifically, this interaction triggers osteoblast-specific expression of alkaline phosphatase and osteocalcin mRNAs, and ultimately, mineralization of bone tissue in a stage-specific sequence [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Homing, growth and differentiation of stem cells after MI is known to depend on the environment in the heart, and especially on the adhesion factors at the site of injury, all of which change dramatically after MI (Lu et al 2004;Malek et al 2006;Wang and Sjoquist 2006;Chastain et al 2006;Salasznyk et al 2004). Therefore, stem cell therapy has to be applied at the moment after infarction when the environment is most favourable for stem cell adhesion and cardiomyocyte formation.…”
mentioning
confidence: 99%
“…Therefore, stem cell therapy has to be applied at the moment after infarction when the environment is most favourable for stem cell adhesion and cardiomyocyte formation. Two extracellular matrix (ECM) molecules of human mesenchymal stem cells are important for stem cell survival and differentiation towards other lineages: laminin and fibronectin (Hashimoto et al 2006;Salasznyk et al 2004;Wijelath et al 2004). Both these proteins are expressed in the normal heart and increase after MI (Froen and Larsen 1995;Knowlton et al 1992;Willems et al 1996).…”
mentioning
confidence: 99%